MRN complex is an essential effector of DNA damage repair - QIU, Shan (J Zhejiang Univ Sci B, 2021)
Genome stability can be threatened by both endogenous and exogenous agents. Organisms have evolved numerous mechanisms to repair DNA damage, including homologous recombination (HR) and non-homologous end joining (NHEJ). Among the factors associated with DNA repair, the MRE11-RAD50-NBS1 (MRN) complex (MRE11-RAD50-XRS2 in Saccharomyces cerevisiae) plays important roles not only in DNA damage recognition and signaling but also in subsequent HR or NHEJ repair. Upon detecting DNA damage, the MRN complex activates signaling molecules, such as the protein kinase ataxia-telangiectasia mutated (ATM), to trigger a broad DNA damage response, including cell cycle arrest. The nuclease activity of the MRN complex is responsible for DNA end resection, which guides DNA repair to HR in the presence of sister chromatids. The MRN complex is also involved in NHEJ, and has a species-specific role in hairpin repair. This review focuses on the structure of the MRN complex and its function in DNA damage repair.